Pope Francis and his call for a new economic model: The anthropological criterion - Macaraan, Willard Enrique R. (Journal for the study of religions and ideologies, 2021)
Pope Francis argues for a shift to a new economic model that in the service of the human life and is "more attentive to ethical principles" (LS 189). He does not endorse a specific model except that he provides conditions, principles, and frameworks by which its ethos must be grounded against. As part of his pastoral approach and his vision of a synodal Church, he invites everyone to participate and contribute to this discussion because "not all discussions of doctrinal, moral or pastoral issues need to be settled by interventions of the magisterium" (AL 3). It is within this papal invitation of discoursing this new economic model where this paper aims to contribute particularly on the centrality of the anthropological criterion. The first section explores the meaning of his articulation on economics; situating it within the economic discourse of Pope John Paul II and Pope Benedict XVI. The second section focuses on the anthropological criterion as problematized by the identification of the homo economicus as self-interested. The third section draws a theoretical framework from substantivist economics in forwarding the desired economic ethos while the fourth section provides praxeological inputs and argues that homo economicus can be pro-social when the culture that is embedded in a particular economic model is put together to nurture such ethos.